Seeking out the land - Safrai, Zeev (Brill, 2018)
Seeking out the Land describes the study of the Holy Land in the Roman period and examines the complex connections between theology, social agenda and the intellectual pursuit. Holiness as a theological concept determines the intellectual agenda of the elite society of writers seeking to describe the land, as well as their preoccupation with its physical aspects and their actual knowledge about it. Ze'ev Safrai succeeds in examining all the ancient monotheistic literature, both Jewish and Christian, up to the fourth century CE, and in demonstrating how all the above-mentioned factors coalesce into a single entity. We learn that in both religions, with all their various subgroups, the same social and religious factors were at work, but with differing intensity.
10.1163/9789004334823
Keywords: Samaritaner; Literatur; Christentum; Rabbinische Literatur; Palästina; Historische Geografie